The king and i - Brackett, Charles; Lang, Walter; Kerr, Deborah; Brynner, Yul ([S.l.] : Cinemascope Pictures)
Musical comedy-drama. A gentle but plucky English widow who, with her ten-year-old son, goes to Siam in 1862 to educate the King's wives and children in the ways of western culture subtly influences the volatile King, whose avidity for scientific knowledge and enlightenment often conflicts with his traditional arrogance and his adherence to the semi-barbaric customs of his country
Based on the book Anna and the King of Siam, by Margaret Landon
Subtitles in Mandarin
Title from title screen
Acquisition for KPI (Kelab Pencinta Ilmu)
Academy awards 1956 : Best actor, Yul Brynner ; best art direction (color), Lyle R. Wheeler, John DeCuir ; set decoration (color), Walter M. Scott, Paul S. Fox ; best costume design, Irene Sharaf ; best sound recording, 20th century FOX sound department, Carl Faulker ; best scoring pf a musical picture, Alfred Newman, Ken Darby
Screenplay, Ernest Lehman ; music, Richard Rodgers
Keywords: Musicals -- Librettos; Musical films